Traditional Values and Educational Access: A Study of Girls' Schooling Rights in Pakpak Cultural Communities - Sudarwati, Lina; Hadriana; Napsiah, Napsiah; Erika; Tengku; Mohammad (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: this research examines the intricate processes contributing to educational development inequity among girls from impoverished female-headed households (pekka) in Pakpak communities at Pegagan Julu VIII Village, North Sumatra. The study explores the interplay between cultural traditions, socioeconomic constraints, and gender ideology that restricts girls' educational opportunities despite Indonesia's commitment to gender equality in educational development frameworks. Method: the investigation employed qualitative feminist methodology, gathering comprehensive life stories from seven Pakpak girls (ages 15-20) who experienced educational discontinuation. Data collection involved in-depth interviews, participatory observation, and focus group discussions with participants and their families, conducted over nine months of ethnographic fieldwork. Results: the analysis revealed that educational development inequity stems from two interlocking systems: patriarchal cultural structures and extreme poverty conditions. These systems create a